2010
DOI: 10.1128/jcm.02002-09
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus (HEV) Strains in Serum Samples Can Replicate Efficiently in Cultured Cells Despite the Coexistence of HEV Antibodies: Characterization of HEV Virions in Blood Circulation

Abstract: We recently developed a cell culture system for hepatitis E virus (HEV) in PLC/PRF/5 and A549 cells, using fecal specimens from HEV-infected patients. Since transfusion-associated hepatitis E has been reported, we examined PLC/PRF/5 and A549 cells for the ability to support replication of HEV in various serum samples obtained from 23 patients with genotype 1, 3, or 4 HEV. HEV progenies emerged in culture media of PLC/PRF/5 cells, regardless of the coexistence of HEV antibodies in serum but dependent on the loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
284
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(298 citation statements)
references
References 61 publications
(77 reference statements)
11
284
1
2
Order By: Relevance
“…Genotypes 2 and 4 HEVs have not yet been examined for the function of the ORF3 protein on virion egress by using infectious cDNA clones. However, given their conservation, and since the association of HEV virions of genotypes 1, 3 or 4 in blood circulation with ORF3 protein and lipids on the surface has been noted (Takahashi et al, 2010), it is very likely that the function of the ORF3 protein related to HEV morphogenesis is common to all HEV strains, irrespective of genotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genotypes 2 and 4 HEVs have not yet been examined for the function of the ORF3 protein on virion egress by using infectious cDNA clones. However, given their conservation, and since the association of HEV virions of genotypes 1, 3 or 4 in blood circulation with ORF3 protein and lipids on the surface has been noted (Takahashi et al, 2010), it is very likely that the function of the ORF3 protein related to HEV morphogenesis is common to all HEV strains, irrespective of genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study using an ORF3-deficient cDNA clone of pJE03-1760F/ wt revealed that the ORF3 protein is essential for virion egress from infected cells (Yamada et al, 2009a). Furthermore, the ORF3-null mutant produced virus particles with the same buoyant density (1.26-1.27 g ml 21 in sucrose) as faecal HEV, which were clearly different from the cell culture-generated wild-type virions and those in the circulation of infected individuals, which banded at 1.15-1.16 g ml 21 and are intimately associated with lipids and the ORF3 protein (Yamada et al, 2009a;Takahashi et al, 2008bTakahashi et al, , 2010. These observations suggest that the acquisition of host-cell membrane on the surface of the virions is dependent on the expression of the ORF3 protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takahashi et al (24) recently showed that virtually any serum with a high HEV titer can infect cultured cells. RNA viruses exist as quasispecies, and, given the tremendous difficulties in developing a cell culture system for HEV, it appears that a sample with a high titer has an increased probability of containing a variant with the correct constellation of mutations needed to permit infection of a cultured cell.…”
Section: Discussionmentioning
confidence: 99%
“…HEV is a non-enveloped small virus with a diameter of 27-32 nm, present in the bile and faeces of infected hosts, while HEV particles in the circulating blood and culture supernatant are found to be associated with lipids (Takahashi et al, 2008b(Takahashi et al, , 2010Yamada et al, 2009a). The HEV genome is a positive-sense, ssRNA composed of approximately 7200 nt, which is capped and polyadenylated (Kabrane-Lazizi et al, 1999;Tam et al, 1991).…”
Section: Introductionmentioning
confidence: 99%